EVALUATION OF THE HEALTH OF STATE-OWNED ENTERPRISES THROUGH THE ROLE OF RATING AGENCIES IN ENSURING FINANCIAL PERFORMANCE AND STABILITY: A LITERATURE REVIEW OF FINANCIAL INDICATORS, CORPORATE GOVERNANCE, AND PUBLIC TRANSPARENCY - Era Purike (Adisam Publisher, 2025)
This study aims to evaluate the health of State-Owned Enterprises (SOEs) through the role of rating agencies in ensuring financial performance and stability by examining three main dimensions, namely financial indicators, corporate governance, and public transparency. The research method used is library research with a qualitative descriptive approach that focuses on conceptual analysis of various scientific sources, rating agency reports, and government regulations on SOE governance. The results of the study show that financial indicators serve as objective benchmarks in assessing operational efficiency and sustainability, while corporate governance plays a role in maintaining accountability and internal control. On the other hand, public transparency strengthens public and investor confidence in state financial management. Rating agencies play an important role as external supervisors that provide objective assessments of SOE health and encourage the creation of a corporate culture that is transparent, professional, and performance-oriented. The synergy between strengthening financial indicators, implementing good governance, and public information disclosure under the supervision of independent rating agencies has proven to be the main foundation for the sustainability and competitiveness of SOEs at the national and global levels.